Operation plan for the Iceland-Syowa conjugate campaign in 1983-1985 - Sato, Natsuo; Fukunishi, Hiroshi; Saemundsson, Th. (1984)
P(論文) Geomagnetic conjugate points of Syowa, Mizuho and Molodezhnaya Stations in Antarctica are located in the vicinity of Husafell, Isafjordur and Husavik in Iceland. This campaign aims at a further understanding of physical processes in auroras and their related phenomena from coordinated observations of magnetic field variations, magnetic ULF waves, ELF-VLF emission, cosmic noise absorption and spatial and temporal variations of auroras at these three pairs of geomagnetic conjugate stations. This paper gives an outline of the campaign schedule, the location of three observatories to be set up in Iceland and the specifications of facilities. departmental bulletin paper